Pengembangan Modul Ajar Berdiferensiasi Berbasis Kemandirian Belajar Terhadap Kemampuan Komunikasi Matematis Pada Materi Teorema Pythagoras - Selvina Lian; Muchtadi Muchtadi; Utin Desy Susiaty (LPD Universitas PGRI Pontianak, 2026)
Abstract: This study aimed to develop a differentiated teaching module based on self-directed learning for the Pythagorean Theorem topic to improve students' mathematical communication skills. The study employed a Research and Development (R&D) approach using a modified 3D development model consisting of the Define, Design, and Develop stages. The research subjects were Grade VIII students of SMP YPK Pontianak. The research instruments included validation sheets, practicality questionnaires, and mathematical communication skill tests. Data were analyzed using descriptive qualitative and quantitative methods. The results indicated that the developed teaching module met the criteria of validity, practicality, and effectiveness. The average validation score from experts reached 85%, indicating that the module was valid for implementation. The practicality test showed an average score of 88.4%, categorized as very practical based on teachers' and students' responses. Furthermore, the effectiveness test demonstrated an N-Gain score of 0.60 (moderate category) with 80% classical learning completeness, indicating that the module effectively improved students' mathematical communication skills. Therefore, the differentiated teaching module based on self-directed learning is feasible to be used as an alternative teaching material in mathematics learning, particularly on the Pythagorean Theorem topic. Keywords: Differentiated Teaching Module, Self-directed learning, Mathematical Communication Skills, Pythagorean Theorem, Research and Developmentl.